Analysis of A Tall Structure Considering Base Isolators Using ETABS : A Review - Patil, Shravan Kumar Sahu; Patil, Pradeep Kumar; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2024)
Safety of people in a building depends on capability of the building to resist earthquake waves and then stands upright after earthquake situation without or with few damage and maintenance. Various systems like dampers, base isolators, shear wall, elevated water tank, etc., are use to dissipate seismic energy. Effectiveness of these systems is based on its type and position of these elements. In this paper, we are conducting a research on “base isolators”.